Electoral behavior of the Russian youth - K. G. Ustinkin (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
There are considered the peculiarities of electoral behavior of modern Russian youth depending on social origin, income level, social environment, education, age, and also analyzes the readiness of the youth electorate motivated to implement electoral activities.